LEGAL REVIEW FOR PERPETRATORS OF THE CRIMINAL ACTS OF EXPLOITATION OF HUMAN TRAFFICKING BASED ON THE TPPO LAW (Study of Case Decision Number: 2400/Pid.Sus/2023/Pn.Mdn) - Ganda Permana Ketaren; Chairuni Nasution; Yasmirah Mandasari Saragih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
In Indonesia, since the beginning of independence, the government has created the 1945 Constitution which includes protection for all Indonesian people and provides welfare for its citizens. The problem of "human trafficking" has now become a public problem that must be immediately addressed by the government, both central and regional, because without any action taken by the government in anticipating and handling this human trafficking case, it is feared that it will continue to extend the series of human trafficking cases. The formulation of the problem drawn in this study is how the criminal sanctions for perpetrators of human trafficking are based on the laws and regulations in force in Indonesia, How is the Author's Analysis of the application of the law for perpetrators of human trafficking crimes based on the study of Court decisions number: 2400 / pid.sus / 2023 / Pn.Mdn The research method carried out in this study is research using descriptive normative studies, namely describing, finding legal facts in full and systematically examining the problems studied. The results in this study, the Author has a different view of the Decision given by the judge, especially regarding the reduction of the defendant's sentence. This article also compares the Human Trafficking Law with Law Number 1 of 2023 which provides several changes in the eradication of human trafficking crimes.